ANALISIS PERAN AGEN DALAM MENINGKATKAN JUMLAH NASABAH DAN PANGSA PASAR PADA PT. PEGADAIAN (Persero) UPC TONGAS KABUPATEN PROBOLINGGO - Maylani, Dian; Selfiya, Selfiya; Ningtiyas, Septi Diah Ayu; Fatimatuzzahro, Fatimatuzzahro (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
PT. Pegadaian (Persero) is a non-bank financial institution that has the legal authority to finance loans on a pawn basis. The aim of this research is to analyze the role of agents in increasing the number of customers and expanding market share at PT. Pegadian (Persero) UPC Tongas, Probolinggo Regency. The research method used is qualitative with a descriptive approach of case studies at pawnshops. Data collection techniques used include interviews, observation, secondary data and documentation. Findings show that pawnshops are business partners of the company, this is one of Pegadian's marketing strategies. Pegadian agents play an important role in increasing the customer base by expanding market reach and increasing sales volume through distribution channels. Research also shows that pawnshop agents' performance improves when their own income increases. Therefore, Pegadian must provide ongoing training to keep agents motivated and maintain the quality of their sales channels. Therefore, the role of agents in the financial industry has a significant impact on whether companies can achieve higher profits through effective distribution channels. Keywords: Agent Role, Number of Customers, Market Share, Pawnshop